2019
DOI: 10.3390/atmos10100580
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Behaviour of Human Thermal Indices under Divergent Atmospheric Conditions: A Sensitivity Analysis Approach

Abstract: This paper aims to analyse and conclude about the behaviour of the most commonly used human thermal comfort indices under a variety of atmospheric conditions in order to provide further information about their appropriateness. Utilising Generalized Additive Models (GAMs), this article examines the indices’ sensitivity when exposed to diverse classified atmospheric conditions. Concentrated upon analysing commonly used human thermal indices, two Statistical/Algebraic indices (Thermohygrometric Index (THI) and HU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Comparatively to the original PET index, and according to Chen and Matzarakis ( 2017 ), such deviations take place as a result of (i) an integrated multiple-segment thermoregulation model (with a total of 15–25 body model nodes, instead of the original two), and (ii) a clothing model that renders a more accurate analysis of the human bio-heat transfer mechanism. Without discrediting the former EBM index, numerous studies have already documented the augmented capacity of mPET to render more precise thermophysiological estimations based on its enhanced efficiency to identify the human heat transfer dynamics between the inner and outer body (e.g., Charalampopoulos and Nouri 2019 ; Chen et al 2020 ; Lin et al 2018 ; Nouri et al 2017 ; Nouri et al 2018b ; Şensoy et al 2020 ; Wu et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Comparatively to the original PET index, and according to Chen and Matzarakis ( 2017 ), such deviations take place as a result of (i) an integrated multiple-segment thermoregulation model (with a total of 15–25 body model nodes, instead of the original two), and (ii) a clothing model that renders a more accurate analysis of the human bio-heat transfer mechanism. Without discrediting the former EBM index, numerous studies have already documented the augmented capacity of mPET to render more precise thermophysiological estimations based on its enhanced efficiency to identify the human heat transfer dynamics between the inner and outer body (e.g., Charalampopoulos and Nouri 2019 ; Chen et al 2020 ; Lin et al 2018 ; Nouri et al 2017 ; Nouri et al 2018b ; Şensoy et al 2020 ; Wu et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…GIS-based methodology to evaluate green roofs and green urban areas 9 [4][5][6][7][8][9][10][11][12] Outdoor thermal comfort: UHI mitigation strategies and thermal comfort indexes 20 [2,4,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Energy savings and Indoor thermal comfort from Green roofs 5 [1,[31][32][33][34] 2.…”
Section: No Of Papers Sourcementioning
confidence: 99%
“…Various studies have been conducted to investigate UHI, using, for example, satellite images, surveys, building footprints and morphological parameters [13,23]. Renard et al [22] examined UHI by analysing satellite images, and the study showed that heavy renovations are necessary to achieve a decrease in surface temperature and that the results are related to the increase in green urban spaces.…”
Section: Outdoor Thermal Comfort: Uhi Mitigation Strategies and Thermmentioning
confidence: 99%
See 1 more Smart Citation
“…Although met with some resistance due to the already extensive amount and versatility of existing indices, such studies still salient the continual and important scientific desires to further develop additional approaches to human biometeorology. Adjacently, from the large identified sample of indices, many studies have suggested that only between 6 and 4 thermal indices can provide wholesome local human thermo-physiological evaluations [47,69,[73][74][75]. In addition, and as a distinguished example from many related studies (discussed later in this section), the work undertaken by Lin, Tsai, Hwang and Matzarakis [66] presented important outputs pertaining to crucial relationships with microclimatic variables such as Mean Radiant Temperature (MRT) and Sky View Factor (SVF) ratios.…”
Section: Thermo-physiological and Climatic Indicesmentioning
confidence: 99%